Potensi Lokasi Base Transceiver Station (BTS) Berdasarkan Pemerintah Dan Mayarakat di Kota Mataram - Yunidiya, Dini Rizka; Sutikno, Fauzul Rizal; Dinanti, Dian (Fakultas Teknik, Universitas Brawijaya, 2013)
Base Transceiver Station (BTS) is one of telecommunication facilities which had built for supporting communication technology development. However, the placement of Base Transceiver Station (BTS) often located at inappropriate location so it needs more specific regulation for placement BTS. Mataram city is one of the cities that doesn’t have local regulations regarding the placement of BTS which caused some BTS located at inappropriate place. Based on those conditions, it needs to match the perception from both the government and the society for determining the appropriate location for BTS in Mataram city. The method used in this study is the Analytic Hierarchy Process (HAP) which used government and society representatives as informants. This study uses 14 variables determining the location of BTS that are Land Use Variables (Green Open Space, The Road Network, Commerce and Service, Education, Worship, Health, and Office), Topology (Land Slope), The Population (Population Density), Environmental Aesthetics (Joint Tower and The location of BTS Eksisiting), Safety (The Height of The Tower, The Safety of Flight Operations and cultural heritage, and Density of Buildings). The result of AHP method is priority variables from both of government and society perceptions that would be represent in spatial using overlay method (GIS approach). Then, the result of overlay method which combined perceptions of government and society informants was potential locations for placement of BTS in Mataram city.Keywords: Base Transceiver Station (BTS), Government, Society, Location.